Demographic change and unemployment in East Germany: how close are the ties? - Michaela Fuchs; Antje Weyh (European Regional Science Association (ERSA), 2014)
In East Germany a profound demographic change has been taking place that manifests itself in the shrinkage and the aging of the population. One major cause is the drop in the East German fertility rates by about half directly after the reunification of Germany in 1990. In no other countries of the former Eastern Bloc, this process was so drastic and abrupt as in East Germany. Around the year 2007, the small after-reunification cohorts started to enter the East German labor market that had been characterized for many years by high unemployment and declining employment. Beginning in 2005, however, the situation on the labor market reversed. At the same time, substantial labor market reforms were started in Germany that have additionally spurred employment. Given these developments, the question arises if and to what extent the labor market entry of the young and smaller cohorts has affected the declining unemployment rate in East Germany. This paper tackles the question of the ties between demography and unemployment in East Germany and to this end draws on the concepts of the cohort crowding literature. Using data from official population and labor-market statistics for the period from 1993 to 2012, we calculate both a direct and an indirect effect of aging on unemployment. For the direct effect we decompose the East German unemployment rate in three components. We find that not changes in the age structure of the population but rather labor-market effects had the greatest impact on the decrease in unemployment. For the econometric analysis of the indirect effect, we use information on the small-scale regional level and resort to spatial panel methods. The results yield a strong relation between the youth as well as the old-age dependency ratio and the unemployment ratio. A decline in the youth dependency ratio of one per cent comes along with a decline of the unemployment ratio of 0.489 per cent. Likewise, an increase of the old-age dependency ratio of one per cent is accompanied by a fall of the unemployment ratio of 0.470 per cent. Overall, our results provide evidence that the declining unemployment rate in East Germany is indeed affected by aging. Thus, a reversed cohort crowding effect has been taking place in the East German labor market.
Keywords: C21; J21; J82; R23; 330; Demographic change; Unemployment; East Germany; Spatial panel methods